2009
DOI: 10.1177/0040517508095608
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology and Properties of Bombyx mori Silk Fibroin Fiber Treated with I 2-KI Aqueous Solution

Abstract: .jp ABSTRACTThe surface morphology, thermal and mechanical properties of Bombyx mori silk fibroin (SF) fiber treated with a 1.23 N iodine-potassium iodide (I 2 -KI) aqueous solution were investigated using scanning electron microscopy (SEM), atomic force microscopy (AFM), differential scanning calorimetry (DSC), thermogravimetric (TG) analysis, and tensile measurements to clarify the effects of the iodine treatment. SEM and AFM analyses indicated that the SF fiber surface became rougher by the absorption of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…SEM was used to evaluate the alteration of the surface morphology of the SDI and SP samples. SP samples shows smooth surface morphology compared to the SDI which is consistent with earlier SEM studies of silk fibers as shown in Figure a, b . Surface roughing and flecks seen on the surface of SDI fibers might be due to the effect of DMDF-I 2 cross-linking.…”
Section: Results and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…SEM was used to evaluate the alteration of the surface morphology of the SDI and SP samples. SP samples shows smooth surface morphology compared to the SDI which is consistent with earlier SEM studies of silk fibers as shown in Figure a, b . Surface roughing and flecks seen on the surface of SDI fibers might be due to the effect of DMDF-I 2 cross-linking.…”
Section: Results and Discussionsupporting
confidence: 89%
“…SP samples shows smooth surface morphology compared to the SDI which is consistent with earlier SEM studies of silk fibers as shown in Figure 5a, b. 46 Surface roughing and flecks seen on the surface of SDI fibers might be due to the effect of DMDF-I 2 cross-linking. EDX for SDI sample showed the atomic weight percentage of Iodine on the surface of fibers as 32.58 and in the core as 9.15 with respect to carbon and oxygen (Figure 5c).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Collectively, these have aided in tissue healing and have altered the post-healing properties of the approximated tissue. [4,5] Sensing sutures integrated with ultra-thin electronic components have also been reported that have the ability to sense important parameters (e.g., heat, pH, and bacterial counts) related to wound healing or infection. [6] However, challenges still remain in the development of such advanced sutures.…”
Section: Doi: 101002/adma202004733mentioning
confidence: 99%